2019
DOI: 10.1108/jedt-07-2019-0182
|View full text |Cite
|
Sign up to set email alerts
|

A scan to as-built building information modeling workflow: a case study in Malaysia

Abstract: Purpose Three dimensional (3 D) laser scanner surveying is widely used in many fields, such as agriculture, mining and heritage documentation and can be of great benefit for as-built documentation in construction and facility management domains. However, there is lack of applied research and use cases integrating 3 D laser scanner surveying with building information modeling (BIM) for existing facilities in Malaysia. This study aims to develop a scan to as-built BIM workflow to use 3 D laser scanner surveying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…e method of converting 3D scanning point cloud data of existing buildings into BIM model is known as scan-to-BIM [29]. From the perspective of academic value, the application of point cloud technology in the construction industry is still at the initial stage, and there is still no unified standard or application mode.…”
Section: Scan-to-bimmentioning
confidence: 99%
See 1 more Smart Citation
“…e method of converting 3D scanning point cloud data of existing buildings into BIM model is known as scan-to-BIM [29]. From the perspective of academic value, the application of point cloud technology in the construction industry is still at the initial stage, and there is still no unified standard or application mode.…”
Section: Scan-to-bimmentioning
confidence: 99%
“…e processing of point cloud data required to scan a target building with a 3D laser scanner has been discussed in detail in previous studies [26,29,30]. e application process of 3D laser scanning technology is shown in Figure 1.…”
Section: Scan-to-bimmentioning
confidence: 99%
“…In this systematic mapping study, we observed that 32 studies out of 55 were not empirically validated [8]- [11], [20], [23]- [29], [44]- [48], [56], [60][29], [30], [54], [55], [61], [34], [36]- [38], [40], [42], [43], [53], which amount to 58.18% of the selected studies. We come to this conclusion by taking two things into consideration, which are the performance measure and simulation tool of a given study.…”
Section: G Rq7: Are the Selected Studies Empirically Validated?mentioning
confidence: 99%
“…The first form of LiDAR technology was introduced in 1961 which was initially intended for satellite tracking. By calculating the return time of emitted lasers, by using sensors and data acquisition electronics, the distance of two points can be measured (Rahman et al, 2019). Today, LiDAR technology has improved significantly, by utilizing a LiDAR scanner unit that can rotate on an axis on a tripod, known as TLS (Terrestrial Laser Scanner) unit.…”
Section: Introductionmentioning
confidence: 99%